Modulation of Gut Microbial Community and Metabolism by Dietary Glycyl-Glutamine Supplementation May Favor Weaning Transition in Piglets - Yan, Yiqin; Xu, Baoyang; Yin, Boqi; Xu, Xiaofan; Niu, Yaorong; Tang, Yimei; Wang, Xinkai; Xie, Chunlin; Yang, Tao; Zhou, Shuyi; Yan, Xianghua; Ma, Libao (Frontiers in Microbiology, 2020)
Gut microbiota plays a crucial role in diet nutrient metabolism and maintaining host health. The synthetic dipeptides glycyl-glutamine (Gly-Gln) used as diet supplementation to improve the weaning transition of newborns could be metabolized by certain bacteria in vitro. However, the effect of diet Gly-Gln supplementation on gut microbiota in vivo remains largely unknown. 240 piglets at the age of 28 days (day 28) were randomly assigned to two groups that received a basal diet (Ctrl group) or a basal diet supplemented with 0.25% Gly-Gln (Gly-Gln group) for 3 weeks. Five piglets from each group were euthanized for sampling after overnight fasting on day 38 and day 49, respectively. We determined their structure shifts of the gut microbiota using 16S rDNA-based high-throughput sequencing analysis. Microbial metabolites short-chain fatty acids (SCFAs) in the ileum and the colon were determined with high-performance gas chromatography. The concentrations of endocrine peptides including epidermal growth factor, glucagon-like peptide-1, and glucagon-like peptide-2 in ileal mucosa, as well as the serum concentration of interleukin 1 beta, interleukin 6, interleukin 10, and tumor necrosis factor alpha were determined using Enzyme-Linked Immunosorbent Assay. In addition, we also checked the diarrhea ratio, growth performance, and intestinal morphology to assess the favorable effect of dietary Gly-Gln supplementation during the weaning transition. Dietary Gly-Gln supplementation beneficially altered the gut microbiota by increasing bacterial loading, elevating alpha diversity, and increasing the relative abundance of anaerobes and fiber-degrading bacteria (Phylum Fibrobacteres). Accordingly, the microbial metabolites SCFAs in both colon and ileum, as well as the downstream endocrine peptides in the ileum increased. Meanwhile, dietary Gly-Gln’s favorable weaning transition was reflected in the increase of growth performance indices and the reduced inflammatory response in a time dependent manner. There were significant correlations among the bacteria which responded to dietary Gly-Gln supplementation and these checked indices. Taken together, dietary Gly-Gln supplementation selectively modulated the gut microbiota, which may favor piglets’ weaning-transition. These findings suggest that gut microbiota targeted approaches can be potentially used to improve weaning transition of piglets by dietary functional amino acid.